A Hybrid Electrode of Co3O4@PPy Core/Shell Nanosheet Arrays for High-Performance Supercapacitors - Yang, Xiaojun; Xu, Kaibing; Zou, Rujia; Hu, Junqing (Nano-Micro Letters, 2015)
Herein, combining solverthermal route and electrodeposition, we grew unique hybrid nanosheet arrays consisting of Co3O4 nanosheet as a core, PPy as a shell. Benefiting from the PPy as conducting polymer improving an electron transport rate as well as synergistic effects from such a core/shell structure, a hybrid electrode made of the Co3O4@PPy core/shell nanosheet arrays exhibits a large areal capacitance of 2.11 F cm−2 at the current density of 2 mA cm−2, a ~4-fold enhancement compared with the pristine Co3O4 electrode; furthermore, this hybrid electrode also displays good rate capability (~65 % retention of the initial capacitance from 2 to 20 mA cm−2) and superior cycling performance (~85.5 % capacitance retention after 5000 cycles). In addition, the equivalent series resistance value of the Co3O4@PPy hybrid electrode (0.238 Ω) is significantly lower than that of the pristine Co3O4 electrode (0.319 Ω). These results imply that the Co3O4@PPy hybrid composites have a potential for fabricating next-generation energy storage and conversion devices.